Experience report: Teamwork, interdisciplinarity and interprofessionality in three multi-professional residence centers in Brazil (Research, Society and Development, 2023)
Introduction Multidisciplinary residency is a relatively recent activity in the Brazilian healthcare universe. Working as a team in health services where the hierarchy and verticalization of professions are dominant remains a major challenge, as does acting in an interprofessional manner. Over time, Multiprofessional Residency Programs have developed actions to expand their operations and influence in the health system. One of the instruments to carry out this task is the implementation of teamwork, interdisciplinary and interprofessional. This article aims to present the current form of organization of three multidisciplinary residency centers located in different units of the Brazilian federation, with regard to teamwork, interdisciplinary and interprofessional action, and answer the question whether or not interprofessional work occurs in each of the aforementioned centers. Methodology The Experience Report was used to describe team, interdisciplinary and interprofessional work in each residency center. Results and discussion Each center develops work within the scope of the multidisciplinary residency in different ways. The development of interdisciplinarity occurs at specific moments, especially in the construction of case studies, as dialogue between professionals and the construction of intervention projects with integral and specific objectives for each user is identified. Some programs use the Singular Therapeutic Project as a strategy for this purpose, however, interprofessionality is not verifiable. Conclusion The interdisciplinary and interprofessional proposal is rather a challenge, which, due to shared questioning, tends to converge with reciprocity, mutual enrichment and joint learning between individuals who interact interdisciplinary.